2016
DOI: 10.1186/s13046-015-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

Maspin enhances cisplatin chemosensitivity in bladder cancer T24 and 5637 cells and correlates with prognosis of muscle-invasive bladder cancer patients receiving cisplatin based neoadjuvant chemotherapy

Abstract: BackgroundMaspin, a non-inhibitory member of the serine protease inhibitor superfamily, has been characterized as a tumor suppressor gene in multiple cancer types. Chemotherapeutic insensitivity is one of major obstacles to effectively treating muscle invasive bladder cancer (MIBC). This study was conducted to investigate the role and probable mechanism of Maspin enhancing cisplatin chemosensitivity of bladder cancer in vitro and MIBC patients.MethodsMaspin expression was quantified by qRT-PCR in two MIBC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
(37 reference statements)
2
28
0
Order By: Relevance
“…Additional MTS and apoptosis assays revealed that ectopic maspin overexpressed in T24 (T24-Maspin) cells was more sensitive to cisplatin-induced apoptosis than mock-transfected T24 cells were (Figure 2E,F). These results are consistent with those of other studies reporting that the ectopic overexpression of maspin improved the sensitivity of bladder carcinoma cells to cisplatin [23,24]. Moreover, our study demonstrated that maspin blocked tumor growth in vivo when using xenografts of BALB/cAnN-Foxn1 NU mice (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…Additional MTS and apoptosis assays revealed that ectopic maspin overexpressed in T24 (T24-Maspin) cells was more sensitive to cisplatin-induced apoptosis than mock-transfected T24 cells were (Figure 2E,F). These results are consistent with those of other studies reporting that the ectopic overexpression of maspin improved the sensitivity of bladder carcinoma cells to cisplatin [23,24]. Moreover, our study demonstrated that maspin blocked tumor growth in vivo when using xenografts of BALB/cAnN-Foxn1 NU mice (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…It has become the fourth most common tumor among men with morbidity almost 4 times than that among women [ 1 ]. Approximately 70 % of patients present non-muscle invasive bladder cancer (NMIBC) and patients with muscle-invasive bladder cancer (MIBC) account for the rest [ 2 , 3 ]. Transurethral resection of bladder tumor (TURBT) and intravesical chemotherapy usually have been chosen to treat NMIBC, while radical cystectomy is used for high-grade muscle-invasive bladder cancer (MIBC).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms that mediate cisplatin resistance have been identified, including decreased import, pronounced activity of efflux pumps, increased detoxification, and increased efficiency of DNA repair systems [ 32 35 ]. Since DNA damage and the induction of mitochondrial apoptosis are the most critical mechanisms of cisplatin action, evasion of apoptosis might be a key feature of acquired cisplatin resistance in tumor cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%